Nonconservative Stability Problems of Modern Physics. - Kirillov, Oleg N. (De Gruyter studies in mathematical physics., 2013)
This work gives a complete overview on the subject of nonconservative stability from the modern point of view. Relevant mathematical concepts are presented, as well as rigorous stability results and numerous classical and contemporary examples from mechanics and physics. The book shall serve to present and prospective specialists providing the current state of knowledge in this actively developing field. The understanding of this theory is vital for many areas of technology, as dissipative effects in rotor dynamics orcelestial mechanics.